(untitled) (Revista do Centro de Estudos Portugueses, 2002)
A obra de Guimarães Rosa deixa transparecer sinais da construção de seu imaginário. Uma das chaves desse processo pode ser buscada na correspondência do escritor com o pai, revelando-se este último um manancial de torneios verbais, tipos humanos e anedotas sertanejas. The writing of Guimarães Rosa keep traces of the elaboration of its imaginary world. A key to this process can be searched in the correspondence between the writer and his father, in which the latter is taken as a source of verbal manner, human types and backlands anecdotes.